2022
DOI: 10.3390/pharmaceutics14091979
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides and Biomarkers Induced by Ultraviolet Irradiation Have the Potential to Reduce Endodontic Inflammation and Facilitate Tissue Healing

Abstract: Background: Ultraviolet (UV) irradiation can modulate host immune responses and this approach is a novel application for treating endodontic infections and inflammation in root canals. Methods: A dataset of UV-induced molecules was compiled from a literature search. A subset of this dataset was used to calculate expression log2 ratios of endodontic tissue molecules from HEPM cells and gingival fibroblasts after 255, 405, and 255/405 nm UV irradiation. Both datasets were analyzed using ingenuity pathway analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Furthermore, the analysis of protein interactions indicated that Livin expression influenced the expression of keratins (Figure 5A). Keratin 14 and 17 are known to be elevated in UVB‐induced skin photodamage, impacting epidermal barrier function 16,17 . In this study, UVB exposure at 250 mJ/cm 2 did not result in elevations in keratin 17 and keratin 14 levels in Livin fl/fl mice.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…Furthermore, the analysis of protein interactions indicated that Livin expression influenced the expression of keratins (Figure 5A). Keratin 14 and 17 are known to be elevated in UVB‐induced skin photodamage, impacting epidermal barrier function 16,17 . In this study, UVB exposure at 250 mJ/cm 2 did not result in elevations in keratin 17 and keratin 14 levels in Livin fl/fl mice.…”
Section: Resultsmentioning
confidence: 49%
“…Keratin 14 and 17 are known to be elevated in UVB-induced skin photodamage, impacting epidermal barrier function. 16,17 In this study, UVB exposure at 250 mJ/cm 2 did not result in elevations in keratin 17 and keratin 14 levels in Livin fl/fl mice. In contrast, these levels were significantly elevated in Livin ΔKC mice (Figure 5B).…”
Section: Analysis Of Livin In a Mouse Model Of Uvb-induced Skin Photo...mentioning
confidence: 49%
See 1 more Smart Citation
“…Many of these molecules are related to the wound-healing signaling pathway and communication between immune cells and antimicrobial response. They concluded that, also via the UV irradiation technique, AMPs production requires part of the activate innate immune response with a final aim to reduce infection but also assist tissue healing [27].…”
mentioning
confidence: 99%